RELATIONSHIP BETWEEN LUNG FUNCTION AND INTERLEUKIN-6 (IL-6) LEVELS IN THE POPULATION IN THE VICINITY OF THE GANDUS RUBBER FACTORY AND THE SUKAWINATAN WASTE DISPOSAL SITE IN PALEMBANG - Adela, Novita; Zulkarnain, Mohammad; Flora, Rostika (Biomedical Journal of Indonesia, 2019)
Exposure to air pollution can interfere with the capacity of lung function and the body's immune system. Lung function capacity is the sum of two or more lung volumes. Interleukin-6 (IL-6) is an inflammatory mediator in respiratory pathogenesis. This study aims to determine the relationship between lung function and Interleukin-6 (IL-6) levels in the population around the Gandus Rubber Factory and Sukawinatan Landfill Palembang. The research design used is the type of correlation or explanatory that is examining the relationship between variables. A total of 72 samples were divided into 2 groups: groups in the Gandus Rubber Factory area and groups in the Sukawinatan Waste Disposal Site (Palembang). Lung function tests were measured using spirometry and Interleukin-6 levels were measured using ELISA examination. Chi square test results showed that there was no significant relationship (p value = 0.001) between lung function in the population around the Gandus Rubber Factory and Sukawinatan Waste Landfill. And there is no significant relationship (p value = 0.337) between Interleukin-6 (IL-6) levels in the population around the Gandus Rubber Factory and Sukawinatan Waste Landfill. Chi Square test results showed that there was no significant relationship (p value = 0.626) between lung function and Interleukin-6 (IL-6) levels in the population around the Gandus Rubber Factory. Chi Square test results showed that there was no significant relationship (p value = 1,000) between lung function and Interleukin-6 (IL-6) levels in the population around the Palembang Sukawinatan Landfill. Conclusions from the results of the study that there is no significant relationship (p <0.05) between levels of Interleukin-6 and Lung Function in the population around the Gandus Rubber Factory and Sukawinatan Landfill Palembang.